HUBUNGAN MINAT BELAJAR DAN KEPERCAYAAN DIRI DENGAN KEMAMPUAN MEMBACA ALQURAN SISWA DI SD NEGERI NO 095243 PERDAGANGAN KECAMATAN BANDAR KABUPATEN SIMALUNGUN - Nilna Mayang Kencana (Jurnal At-Tabayyun, 2018)
Learning interest and confidence of students especially in the ability to read the Quran students is very urgent especially in cultivating religious life of students. The Koran as one element of the scope or educational material of Islamic religion very urgent in daily life. That is, the faith adopted by a person who would later produce a value (as in the case of ' worship, Muādan, and Akhlāk) is sourced from the Koran and Alhadīś. The study uses quantitative research methods conducted on inferential research (in the framework of hypothesis testing) and is the result of concluding conclusions on an error probability of a zero hypothesis rejection. With quantitative methods will be acquired significance of the group differences or the significance of the relationship between the variables studied. Based on the results of empirically seen research proved that learning interest and confidence of students have a relationship to the increase in the ability to read the Koran.